1979
DOI: 10.1002/ange.19790910320
|View full text |Cite
|
Sign up to set email alerts
|

Neuartige Glycale als Synthone für Saccharidsynthesen

Abstract: Verbesserungen der Saccharidsynthese erfordern leicht zugängliche Vorstufen und ein gutes Verknüpfungsverfahren. Diese Forderungen werden von den Glycalen (2) und (3) bzw. ihrer Reaktion mit N‐Iodsuccinimid (NIS) erfüllt. magnified image

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1979
1979
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Additionally, these 1,3‐interactions are influenced by the orientation of the C4–OAc group, and it has been shown that 1,3‐diaxial interactions are stronger when C4–OAc and C3–OAc are located on the same side of the pyranoid ring (i.e., C4–OAc equatorially oriented, C3–OAc axially oriented) 12. The 4 H 5 [lrarr2] 5 H 4 conformational equilibrium in tri‐ O ‐acetyl‐ D ‐galactal ( 4 , Figure 2, a) is therefore shifted toward the 4 H 5 form more strongly than the analogous equilibrium of tri‐ O ‐acetyl‐ D ‐glucal ( 5 , Figure 2 (b), molar fractions in the 4 H 5 conformation in acetone: 88 %13 and 59 %,14 respectively).…”
Section: Ferrier I Rearrangement – An Overviewmentioning
confidence: 99%
“…Additionally, these 1,3‐interactions are influenced by the orientation of the C4–OAc group, and it has been shown that 1,3‐diaxial interactions are stronger when C4–OAc and C3–OAc are located on the same side of the pyranoid ring (i.e., C4–OAc equatorially oriented, C3–OAc axially oriented) 12. The 4 H 5 [lrarr2] 5 H 4 conformational equilibrium in tri‐ O ‐acetyl‐ D ‐galactal ( 4 , Figure 2, a) is therefore shifted toward the 4 H 5 form more strongly than the analogous equilibrium of tri‐ O ‐acetyl‐ D ‐glucal ( 5 , Figure 2 (b), molar fractions in the 4 H 5 conformation in acetone: 88 %13 and 59 %,14 respectively).…”
Section: Ferrier I Rearrangement – An Overviewmentioning
confidence: 99%
“…In addition, a number of other methods are known, such as the base-catalyzed C-5 epimerization of uronic acids, 30 31 the radical C-5 epimerization, 32–34 and the post-hydroboration oxidation reaction of unsaturated sugars. 15,16 However, the disadvantage of most methods is that they require complex post-transformations to obtain donor molecules suitable for glycosylation.…”
Section: Table 1 the Commercial Prices Of ...mentioning
confidence: 99%
“…The starting Dglucuronic acid derivatives were constrained to adopt a conformation having C-6 in an axial position, so that the Liduronic acid derivatives would be thermodynamically more stable. Base-catalyzed epimerization of D-glucuronic acid glycals 20, 21, derived from 19, results mainly in the formation of iduronic acid glycals 22, 23 (ido:gluco 4:1; separable) [25,26]. The low yield in the isomerization step is due to lability under the basic reaction conditions, probably through β-elimination [24].…”
Section: Epimerization Of Anancomeric D-glucuronic Acid Analoguesmentioning
confidence: 99%